Procampylaspis poorei Petrescu 2006, sp. nov. ... - Petrescu, Iorgu (Zenodo, 2006)
Procampylaspis poorei sp. nov. Figures 45, 46 Material examined. Holotype female, Antarctica, Eastern Prydz Bay, off the Larsemann Hills, 68°54.88'S, 76°37.03'E, 667–716 m, epibenthic sled, P.M. OʼLoughlin, RSV Aurora Australis, 18 Feb 1993 (stn AA93 158), NMV J53009. Diagnosis. Carapace with 3 dorsal tubercles, a pair medially and 1 in posterior half, ocular lobe eyeless, close to anterior extremity of pseudorostrum, with spine on top. Maxilliped 2 with 1st dactylar tooth longer than 2nd tooth and shorter than 3rd one, 5th tooth twice as long as 3rd tooth. An inner tooth on ischium of maxilliped 3, 2 teeth on outer margin of merus and carpus. Pereopod 1 with slender articles, merus as long as carpus. Dactylus of 2nd pereopod 2 twice as long as propodus, with plumose setae. Uropod peduncle 1.7 times as long as pleonite 6 and 1.4 times as long as endopod, endopod longer than exopod, with 3 microserrate setae on inner margin. Description. Body with highly calcified integument. Length: 3.8 mm. Carapace 0.46 ... : Published as part of Petrescu, Iorgu, 2006, Nannastacidae (Crustacea: Cumacea) from eastern Bass Strait, the south-eastern Australian slope, and Antarctica in the collections of Museum Victoria, pp. 129-173 in Memoirs of Museum Victoria 63 (2) on pages 158-159, DOI: 10.24199/j.mmv.2006.63.14, http://zenodo.org/record/10665606 ...